2005
DOI: 10.1097/01.iop.0000170421.07098.61
|View full text |Cite
|
Sign up to set email alerts
|

Bowen Disease of the Eyelid Successfully Treated with Imiquimod

Abstract: We present a case of Bowen disease affecting the eyelid that was successfully treated with imiquimod. The clinical presentation, histopathology, and treatment of this case are presented. The tumor was treated with imiquimod for 3 months, leading to complete resolution of the disease both clinically and histopathologically. There was no evidence of recurrence 5 months after treatment cessation. Imiquimod was safely used on the eyelid in this case and may avoid extensive periocular tumor excision and reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Patel et al [6 ] conducted a randomized study to evaluate the efficacy of imiquimod 5% cream to treat biopsy proven squamous cell carcinoma in situ and they achieved 73% of resolution with no relapse during the 9-month follow-up period. Although imiquimod is not approved by the US Food and Drug Administration for the treatment of periocular lesions due to the potential risk of contact with the globe, Brannan et al [7 ] described a patient who was cured after completing a 3-month treatment; the lesion disappeared and no recurrence was noted 6 months postoperatively, but the patient developed a cicatricial lower-lid ectropion that required correction with a skin graft. Although imiquimod seems to be effective for the treatment of Bowen's disease, its use in the periocular area is still controversial.…”
Section: Bowen's Diseasementioning
confidence: 96%
“…Patel et al [6 ] conducted a randomized study to evaluate the efficacy of imiquimod 5% cream to treat biopsy proven squamous cell carcinoma in situ and they achieved 73% of resolution with no relapse during the 9-month follow-up period. Although imiquimod is not approved by the US Food and Drug Administration for the treatment of periocular lesions due to the potential risk of contact with the globe, Brannan et al [7 ] described a patient who was cured after completing a 3-month treatment; the lesion disappeared and no recurrence was noted 6 months postoperatively, but the patient developed a cicatricial lower-lid ectropion that required correction with a skin graft. Although imiquimod seems to be effective for the treatment of Bowen's disease, its use in the periocular area is still controversial.…”
Section: Bowen's Diseasementioning
confidence: 96%
“…also reported cicatricial ectropion after the treatment of Bowen disease with IMQ and the patient underwent surgery for repair of ectropion. [13] We did not observe cicatricial ectropion requiring surgery in our patients.…”
Section: Discussionmentioning
confidence: 52%
“…Concurrent artificial drops, as reported by Blasi et al, were also prescribed for the patient (6). Brannan et al suggested that reducing dosing regimen might reduce side effects (17). Local inflammatory reaction noted in our patient was acceptable in treatment of premalignant condition.…”
Section: Resultsmentioning
confidence: 64%